UPAYA MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VIII SMP SWASTA KRISTEN BNKP TELUKDALAM MELALUI STRATEGI PEMBELAJARAN INKUIRI - Liberkat Solomasi Hulu; Laia, Mitranikasih; Laia, Askarman (Universitas Nias Raya, 2023)
The aim of this research is to determine the improvement in the quality and cognitive learning outcomes of students in semester 1 science subjects class VIII-B BNKP Telukdalam Christian Private Middle School for the 2022/2023 academic year through the application of inquiry learning strategies. This research was implemented at BNKP Telukdalam Christian Private Middle School for the 2022/2023 Academic Year. The subjects in this research were students in class VIII-B with a total of 30 students and the object of this research was the application of inquiry learning strategies. Data collection techniques use tests, observation, questionnaires and interviews. The test used is a multiple choice test which is carried out at the end of each cycle. Based on the results of research on improving science learning outcomes through inquiry learning strategies at BNKP Telukdalam Christian Private Middle School in cycle I with the number of students completing 18 people (60%) out of 30 students with an average score of 60.2 while student learning outcomes in cycle II were The number of students who completed was 23 (76.6%) out of 30 students with an average score of 76.6. The results of observations of student activity in the first cycle at the first meeting obtained an average percentage of 54.6% (less) and at the second meeting the first cycle obtained a percentage of 63.2% which was categorized as sufficient while in the second cycle the student activity at the first meeting increased to 72.6% which was in the good category and at the second meeting increased to 83.5% and is classified in the very good category. Meanwhile, the results of questionnaire processing in cycle I obtained a percentage of 65.2%, including the sufficient category, and in cycle II the percentage of questionnaires increased to 76.82% (good). In conclusion: one of the efforts to improve the learning outcomes of class VIII-B students at the BNKP Telukdalam Christian Private Middle School is to implement inquiry learning strategies. Suggestions: 1) In the learning process, teachers should use inquiry learning strategies in science subjects, 2) Subject teachers should pay attention to weaknesses that occur in the implementation of learning.